(untitled) (International Journal of Engineering and Computer Science, 2014)
The potential and effectiveness of a hybrid intelligent PSS controller combining the advantages of both differential evolution (DE) and tabu search (TS) is assessed in this paper. The controller is incorporated in a single machine infinite bus (SMIB) system with a synchronous generator. An analysis is also carried on the quality of results if various parameters of the differential evolution like crossover, mutation and population size of the algorithm is varied. At the end a comparison is made between the controller based totally on differential evolution and the one designed with the hybrid technique